The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/anie.202008570
|View full text |Cite
|
Sign up to set email alerts
|

HIP to be Square: Simplifying Nitridophosphate Synthesis in a Hot Isostatic Press

Abstract: (Oxo)Nitridophosphates have recently been identified as a promising compound class for application in the field of solid‐state lighting. Especially, the latest medium‐pressure syntheses under ammonothermal conditions draw attention of the semiconductor and lighting industry on nitridophosphates. In this contribution, we introduce hot isostatic presses as a new type of medium‐pressure synthetic tool, further simplifying nitridophosphate synthesis. In a second step, phosphorus nitride was replaced as starting ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…HIPs do not only provide large sample quantities, but also shorten reaction times and facilitate crystal growth under comparatively gentle reaction conditions. Moreover, we have demonstrated that red phosphorus can serve as a starting material in HIPs as well, simplifying nitridophosphate syntheses even more [28] …”
Section: Figurementioning
confidence: 99%
“…HIPs do not only provide large sample quantities, but also shorten reaction times and facilitate crystal growth under comparatively gentle reaction conditions. Moreover, we have demonstrated that red phosphorus can serve as a starting material in HIPs as well, simplifying nitridophosphate syntheses even more [28] …”
Section: Figurementioning
confidence: 99%
“…Die Gruppe von Schnick präsentierte ein neues, schnelles und einfaches Herstellungsverfahren für Nitridophosphate (Abbildung 3). 18) Das Verfahren basiert auf Mitteldruck-heißisostatischem Pressen (HIP). Beispielsweise entstanden damit erstmals Ca 2 PN 3 -Einkristalle.…”
Section: Neue Verbindungenunclassified
“…Already initially used ambient and medium‐pressure (MP) methods ((pressure‐)ampoules, autoclaves) have enabled the preparation of various (oxo/imido)nitridophosphates, phosphorus nitrides, and related compounds [1, 3–10] . The variety of nitridophosphates, which are accessible under MP conditions, has recently been increased by hot isostatic pressing and systematic investigations using high‐temperature ammonothermal methods [2, 11–14] . Despite these advances in MP synthesis, high‐pressure high‐temperature (HP/HT) conditions are still most commonly used for nitridophosphate synthesis [1] .…”
Section: Figurementioning
confidence: 99%